Katoü (wayuu bag) - Fanny Montes (Oñati Socio-Legal Series)
This article presents the exercise of following the katoü or Wayuu bag, critically observing the Colombian-Arijuna (non-Wayuu) society by exploring the representations of the Wayuu territory (as another territory) constructed from positions of power as a hegemonic society, in different strategies of economic intervention in which the katoü becomes a central element. The Wayuu bag turns into an ethnographic magnifying glass for investigating the relationship between Wayuu and Arijuna in a disputed territory in Colombia.